Tomography of regional ventilation and perfusion using krypton 81m in normal subjects and asthmatic patients. - Orphanidou, D (1986)
Single photon emission computed tomography, a rotating gamma camera, and continuous inhalation or infusion of krypton 81m (half life 13 seconds) were used to measure regional ventilation (V), perfusion (Q), and ventilation-perfusion (V/Q) ratios in five normal subjects in supine, prone, and lateral decubitus postures and in three asthmatic patients (supine posture only) before and after inhalation of 2.5 mg nebulised salbutamol. Vertical and horizontal gradients of V, Q, and V/Q were examined at three levels in each lung in regions of 1.9 cm3 size. In normal subjects V and Q increased along the axis of gravity in all postures and at all levels in the lung except for V in the prone position. Smaller horizontal gradients were found with an increase in V and Q from caudal to cranial--again except in the prone posture, where the gradient was slightly reversed. Constraint to outward motion of the ventral chest and abdominal wall is the most likely explanation for the different behaviour in the prone posture. In chronic asthma the vertical gradients of V and V/Q were the reverse of normal, but the Q gradient was normal. Bronchodilator treatment did not affect the vertical or horizontal gradients significantly, but analysis of individual regions showed that, relatively, V/Q worsened in 42% of them; this was associated in two thirds with an increase in fractional Q. After inhalation of beta agonist local vasodilatation may influence V/Q ratios in some units more than bronchodilatation.